2020
DOI: 10.1177/1010539520965280
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Patterns of Antihypertensive Medications in Low- and Middle-Income Countries: A Systematic Review

Abstract: Hypertension is highly prevalent, but its pharmacological management has not been well evaluated in low- and middle-income countries (LMICs). This review examined the prescribing patterns of antihypertensives in LMICs. Data were extracted from a total of 26 studies spanning the time period 2000 to 2018. In 10 studies, calcium channel blockers (CCBs) were the most frequently prescribed medication for managing hypertension (range = 33% to 72%); in 6 studies, renin angiotensin system (RAS) blockers (range = 25% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…Notably, two classes of antihypertensives are used for management [18]. Both calcium channel blockers (CCBs) and angiotensin receptor blockers (ARBs) are predominant [12,18]. The combination of CCBs and ARBs is cost-saving [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, two classes of antihypertensives are used for management [18]. Both calcium channel blockers (CCBs) and angiotensin receptor blockers (ARBs) are predominant [12,18]. The combination of CCBs and ARBs is cost-saving [11].…”
Section: Discussionmentioning
confidence: 99%
“…This could be an informative factor for its preferred use. Ashdad reported that prescribing patterns may not occur according to guidelines in low-and middle-income countries (LMICs) [12], and this could be true, as a few discrepancies were observed in the dataset; however, because the average number of antihypertensive drugs per patient was approximately two (2), it can be said that prescribing patterns are good to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, smoking cessation counseling to hypertensive patients was mentioned by only 4.3% of doctors [ 69 ]. A recent systematic review on prescribing antihypertensive patterns in Pakistan, from a total of 26 studies from 2000 to 2018, concluded that only ten studies utilized national or international guidelines a better understanding of a clinician’s perception and practice of hypertension management guidelines in LMICs is needed [ 70 ].…”
Section: Main Textmentioning
confidence: 99%
“…En el Cuadro 4 se presentan algunas barreras, facilitadores y estrategias de implementación que pueden ser consideradas por los países. (16,20,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) CUADRO 4. Barreras, facilitadores y estrategias para mejorar el cumplimiento de las recomendaciones…”
Section: Conclusionesunclassified